The impact of international financial reporting standards on accounting quality: Evidence from Latin America and the Caribbean [Impacto de los estándares internacionales de información financiera en la calidad contable: Evidencia desde Latinoamérica y el Caribe] (2019)
This paper examines the impact of the application of International Financial Reporting Standards (IFRS) on accounting quality (financial report quality) of Latin American and Caribbean economies, regarding to their local accounting regulatory standards (Local GAAP). By using a sample of listed companies in Latin America and the Caribbean from 2006 to 2016, accounting quality is assessed under three measurement criteria: earnings management, timely loss recognition (accounting attributes) and value relevance (market attributes). The findings suggest a partial accounting quality improvement; it is showed through a decrease on the level of earnings management only after several years of the IFRS application. However, there is no evidence of a greater opportunity to recognize large losses; furthermore, the generated accounting information under IFRS is not valued, with greater usefulness by market agents. © 2019 Universidad Nacional Autonoma de Mexico. All rights reserved.